Legal and Sharia Analysis of Commercial Paper Discounting and Islamic Banking Finance Alternatives - Tunis Abu Bakr Rahman; Widad Mahdi Jasim; Nooruldeen Mustafa Al-Gburi (PT. Islamic Research Publiser, 2026)
This research examines the legal and jurisprudential characterization of commercial paper discounting and explores Sharia-compliant alternatives within the framework of contemporary Islamic banking finance. The study reviews core legal and Fiqh debates surrounding this complex banking operation by analyzing statutory provisions under Iraqi commercial law alongside classical and contemporary Islamic jurisprudential opinions. From a legal perspective, commercial paper discounting is defined as a contractual arrangement whereby a bank advances the value of a commercial instrument prior to maturity in exchange for the transfer of its ownership, with the beneficiary remaining liable to reimburse the bank in the event of default by the original debtor. This characterization classifies discounting as a short-term credit transaction combining consensual contractual elements with endorsement mechanisms. Jurisprudential analysis, however, demonstrates that conventional discounting practices frequently involve prohibited forms of Riba, particularly Riba al-Fadl and Riba al-Nasi’ah, due to the discrepancy between the amount advanced and the nominal value collected at maturity. The study critically evaluates various Fiqh approaches that attempt to classify discounting as an interest-based loan, a sale, or a transfer of rights, highlighting the Sharia shortcomings inherent in each interpretation. As a result, the research proposes viable Sharia-compliant financing alternatives capable of fulfilling similar economic objectives, including Murabaha financing, organized Islamic Tawarruq, and Salam contracts. These alternatives provide lawful liquidity and credit solutions while adhering to Islamic legal principles, demonstrating the possibility of harmonizing modern banking practices with the objectives of Islamic jurisprudence in promoting economic justice and sustainable financial activity.